Implementasi Sistem Usability Scale dalam Evaluasi Usability Tiktok - Silvia; Rahayu Amalia (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
The development of information technology has brought significant changes to how humans interact, one of which is through social media. TikTok has become one of the popular social media applications with various attractive features that support users' creativity and self-expression. This study aims to evaluate the usability level of the TikTok application using the System Usability Scale (SUS) method. This method assesses user experience based on 10 statements rated on a Likert scale ranging from